2007
DOI: 10.1152/ajprenal.00107.2007
|View full text |Cite
|
Sign up to set email alerts
|

Basic fibroblast growth factor modulates proliferation and collagen expression in urinary bladder smooth muscle cells

Abstract: Bladder hypertrophy is a general consequence of bladder outlet obstruction (BOO) and a typical phenomenon observed in clinical urologic diseases such as benign prostatic hyperplasia and neurogenic bladder. It is characterized by smooth muscle hyperplasia, altered extracellular matrix composition, and increased contractile function. Various growth factors are likely involved in hypertrophic pathophysiology, but their functions remain unknown. In this report, the role of basic fibroblast growth factor (bFGF) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
60
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 57 publications
(61 reference statements)
5
60
0
1
Order By: Relevance
“…BSMC were isolated from 9-wk-old female SpragueDawley rats (Japan Slc, Shizuoka, Japan) using a procedure described previously (14,19). Cells after two passages were seeded at 2 ϫ 10 4 cells/ml in six-well plates for Western blot analysis or on chamber slides for immunofluorescence, and then serum-deprived in DMEM containing 0.5% FCS for 48 h before each assay.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…BSMC were isolated from 9-wk-old female SpragueDawley rats (Japan Slc, Shizuoka, Japan) using a procedure described previously (14,19). Cells after two passages were seeded at 2 ϫ 10 4 cells/ml in six-well plates for Western blot analysis or on chamber slides for immunofluorescence, and then serum-deprived in DMEM containing 0.5% FCS for 48 h before each assay.…”
Section: Methodsmentioning
confidence: 99%
“…One is the mechanism of connexin 43 upregulation and the other is the functional involvement of connexin 43 in detrusor hypersensitivity. Regarding the former issue, our previous study demonstrated a regulatory effect of basic fibroblast growth factor (bFGF) on BSMC remodeling in the obstructed bladder with specific alterations of collagen production and BSMC proliferation (14). Since bFGF has been reported to stimulate connexin 43 expression in cardiac myocytes and fibroblasts (7,8), we postulated that the same mechanism that regulates collagen production and cell proliferation could also regulate connexin 43 expression in the obstructed bladder.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the elasticity of the nonshrunken graft should be preserved; this is directly related to development of well-developed and organized smooth muscle bundles derived from the edges of the bladder that traverse the graft, organize and then develop into mature muscles [18].…”
Section: Discussionmentioning
confidence: 99%
“…The opposite face of the scaffold could them be modified using a second component, which in this case was a mixture of PGA and urothelial cells, since these cells could potentially send necessary signals to smooth muscle cells during regeneration. (Beqaj, 2005;Imamura, 2007) When the human bladder smooth muscle cells and urothelial cells where embedded in a PA-scaffold with a growth factor (bFGF) and incubated in vivo in a subcutaneous nude rat model, it was found that the human bladder smooth muscle cells were retained and composed the majority of the scaffold cellular content. It was also found that the system which uses a combination of PGA, PA, growth factors and cells demonstrated higher levels of phenotypic alpha-smooth muscle actin than control scaffolds made of PGA and cells only.…”
Section: Bioactive Peptides and Peptide Amphiphiles For Regeneration mentioning
confidence: 99%